Clinical Characteristics of Intravenous Injection of Monosialotetrahexosyl Ganglioside Sodium-Related Guillain-Barre Syndrome - Shi, Miao; Zhu, Jie; Deng, Hui (Frontiers in Neurology, 2019)
Introduction: Guillain Barre Syndrome (GBS) is an acute inflammatory immune-mediated multiple nerve root neuropathy. GBS primarily damages the spinal nerve root and peripheral nerves, but can also affect the cranial nerves and cause acute demyelination. This study analyzed the clinical features of intravenous injection of monosialotetrahexosyl ganglioside sodium-related Guillain-Barre syndrome (GRD-GBS). Methods: We retrospectively studied 12 patients who developed GRD-GBS after receiving monosialotetrahexosyl ganglioside sodium treatment in association with recent trauma, surgery, acute cerebrovascular disease, or chronic peripheral neuropathy. Clinical characteristics, electrophysiological examinations, serum-specific antibodies, and prognosis were assessed. As controls, we selected 12 patients hospitalized with non-ganglioside-related (NGRD)-GBS. Results: The positive rate of the ganglioside antibody test was significantly higher in the GRD-GBS group (66.67%) than in the NGRD-GBS group (8.33%). CSF protein levels were similar between the groups, but the incidence of blood-nerve-barrier (BNB) disruption was higher in the GRD-GBS group. Patient scores for the Hughes Functional Grading Scale (HFGS), a disability scale, were higher (more severe disability) in the GRD-GBS group than in the NGRD-GBS group. The HFGS scores of the GRD-GBS group did not change between peak onset and 30 days after discharge, but did change significantly by 90 days after discharge, while scores were significantly lower at both 30 and 90 days after discharge in the NGRD-GBS group. Conclusions: GRD-GBS patients showed more severe clinical manifestations, poorer prognosis, and slower recovery than patients with NGRD-GBS. Ganglioside treatment should be used with extreme caution in patients with trauma that damages the BNB.